Periphery of porcine hepatic lobes has the smallest length density of hepatic sinusoids and bile canaliculi: A stereological histological study with implications for liver biopsies - Malečková, Anna; Mik, Patrik; Liška, Václav; Pálek, Richard; Rosendorf, Jáchym; Witter, Kirsti; Grajciarová, Martina; Tonar, Zbyněk (Annals of anatomy, 2023)
BACKGROUND: Porcine liver is widely used in hepatologic research as a large animal model with many anatomical and physiological similarities with humans. However, only limited information on porcine liver spatial microstructure has been published, especially regarding the hepatic sinusoids and bile canaliculi. The aim of our study was to quantify the sinusoidal and bile canalicular network in healthy male and female porcine livers and to map the variability of these structures with heterogenous distribution to improve the evaluability of liver biopsy samples. METHODS: Livers from 12 healthy piglets (6 females and 6 neutered males) were sampled into 36 tissue samples per organ, representing six hepatic lobes and three different regions related to the hepatic vasculature (peripheral, paracaval and paraportal region). Histological sections were processed with a random orientation of the cutting plane. The endothelium and the bile canaliculi were stained using Ricinus communis agglutinin I lectin histochemistry. The length densities of hepatic sinusoids LV(sinusoids,liver), of bile canaliculi LV(bile canaliculi,liver) and volume fraction VV(sinusoids,liver) and surface density SV(sinusoids,liver) of sinusoids were estimated using stereological methods. The newly acquired morphometric data were compared with previously published data on density of porcine hepatocytes and fractions of connective tissue. RESULTS: The peripheral region had smallest LV(sinusoids,liver), smallest LV(bile canaliculi,liver) and greatest VV(sinusoids,liver). The six hepatic lobes had statistically comparable length densities of both sinusoids and bile canaliculi, but the left lateral lobe had smallest VV(sinusoids,liver). Regions with greater LV(sinusoids,liver) had also greater LV(bile canaliculi,liver) and SV(sinusoids,liver) and were accompanied by greater density of smaller hepatocytes. Regions with smaller LV(sinusoids,liver) and LV(bile canaliculi,liver) contained a greater fraction of interlobular connective tissue. CONCLUSIONS: The length density of hepatic sinusoids is smaller in the peripheral regions of the porcine liver than in other regions related to the hepatic vasculature - paracaval and paraportal regions, and smaller in castrated males than in females. Greater length density of liver sinusoids was linked with greater local density of bile canaliculi, with local increase in the density of smaller hepatocytes and, simultaneously, with smaller fractions of hepatic connective tissue. The intrahepatic and inter-sexual variability of the porcine liver morphology needs to be taken into account when designing and interpreting experiments involving the histological quantification of the microvascular network. The complete primary morphometric data describing the distribution of morphometric parameters within porcine liver were made available in a form facilitating the power analysis to justify the minimal number of tissue samples or animals required when designing further histological evaluation studies. The macroscopic map of microvessels and bile canaliculi variability facilitates their assessment in liver biopsies in the pig.
Keywords: žlučové kanálky; Capillaries; játra; Biopsy; Humans; Bile canaliculi; Female; Pig; lidé; zvířata; Bile Canaliculi; biopsie; Swine; ženské pohlaví; Liver; Male; Hepatocytes; Animals; mužské pohlaví; kapiláry; hepatocyty; Stereology; Hepatic sinusoids; prasata